Afecciones podológicas en adultos mayores atendidos en la Consulta de Podología general - Berkis Martínez Rodríguez; Carlos Eddy Lima León; Yaritza Vera Pérez; Aimee Medinas Artiles; Mayelin Ferrer García; Julio Cesar León Granado (Acta Médica del Centro, 2021)
Introduction: foot diseases in the elderly are varied, so that they often suffer from one or several alterations in the same or in both feet, it is stated that 70% of people over 65 years of age have some disorder related to the foot, there being no history of studies in our environment to prove it. Objective: to determine the most frequent podiatric disorders in older adults seen at the podiatry office of the "Chiqui Gómez Lubián" polyclinic. Method: an observational, descriptive, cross-sectional research was carried out with 327 older adults attended in the podiatry office of the polyclinic "Chiqui Gómez Lubián" of Santa Clara municipality. Villa Clara, from January to December 2018. Results: the female sex was the one who most attended consultation and within them the age group from 70 to 79 years, the inadequate use of footwear was found in 67.58% of the population, 80.1% of patients had two or more podiatric conditions, predominantly onicopathies in 90.1% of these, an association was found between hyperkeratosis and deformities of the toes. Conclusions: the female sex was the most affected, the use of inadequate footwear was associated with the appearance of podiatric conditions, which in order of frequency were onychopathies, dermatological conditions and toe deformities.